Availability and use of feed resources in crop-animal systems in Asia - Devendra, C.; Sevilla, C.C. (Elsevier, 2002)
Feed resources and nutrition constitute the principal technical constraints to ruminant production in Asia. Four main categories of feed resources are potentially available for use in smallholder crop-animal systems. These are pastures (native and improved grasses, herbaceous legumes and multi-purpose trees), crop residues, agro-industrial by-products (AIBPs), and non-conventional feed resources (NCFRs). Priorities for the use of crop residues in terms of nutrient potential and animal species are indicated. Of the technologies developed to improve the nutritive value of crop residues, more attention has been given to chemical treatment of cereal straws than to supplementation. However, a failure to demonstrate cost-effectiveness has discouraged on-farm adoption. The production of fodder from food crop systems and the establishment of multi-purpose trees and shrubs are potentially important for insuring adequate feed supplies for ruminants and improving soil fertility, but there has been limited adoption on small farms to date. Equally, there is significant potential for the more effective use of locally-produced AIBPs and NCFRs, all of which are under-utilised currently.